Peranan Modal Intelektual, Kemampuan Membayar Jangka Pendek, dan Keberadaan Komite Audit terhadap Kinerja Keuangan Perusahaan - Izza Mustholih Al Amin; Hijroh Rokhayati (Jurnal Riset Akuntansi Soedirman, 2026)
This study aims to analyze and empirically prove the influence of Intellectual Capital (VAIC™), multidimensional Liquidity, and Audit Committee on Financial Performance proxied by Return on Assets (ROA), integrating Firm Size as a control variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the post-pandemic recovery period from 2022 to 2024. The theories applied in this study are Resource-Based View (RBV), Liquidity Trade-off Theory, and Agency Theory. This is a quantitative causal associative study utilizing secondary data. The population includes 228 manufacturing companies listed on the IDX. Sample selection used a purposive sampling method, resulting in 125 companies and 375 observation units. Outliers were managed using the Winsorizing technique (0.00% to 2.67% adjustment). Data analysis was performed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) with SmartPLS 4 via a 5,000 bootstrapping resampling procedure. The results indicate that: (1) Intellectual Capital (VAIC™) has a positive and significant effect on Return on Assets (ROA), with Human Capital Efficiency (VAHU) as the primary contributor; (2) Liquidity has a positive and significant effect on Return on Assets (ROA), generating a theoretical novelty that holding liquid assets post-pandemic transforms from passive assets bearing opportunity costs into a strategic operational safety buffer; (3) Audit Committee has no effect on Return on Assets (ROA), indicating a formalistic compliance tendency; and (4) Firm Size as a control variable has a positive and significant effect on Return on Assets (ROA).